Usuais: programas para uso em análise ambiental - Oliveira, José Gerardo Beserra de (2016)
The present work has the objetive of presenting to brazilian researchers, a set of computer programs written and employed by researchers at Universidade Federal do Ceará, in order to perform research in Environmental Analysis. The programs are written and compiled in Turbo Basic and are adequate to work in 32 bits versions of Windows operating system. The programs, called USUAIS, are employed with several objectives: i) Studies of individual units of the Environment, such as Pluviometric Stations, Databases and Profiles and Soil Associations, based in their characteristics and locations, and ii) Evaluation of characteristics in digital maps.